1987
DOI: 10.1016/0014-5793(87)80564-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three additional members of rat protein kinase C family: gd‐, ϵ‐ and ξ‐subspecies

Abstract: Three types of cDNA clone of the protein kinase C family termed 6, Eand < were newly identified by molecular cloning and sequence analysis. These members have a common structure that is closely related to, but clearly different from the other four known members of the family which have LX-, PI-, PII-and y-sequences, although the I-cDNA available at present does not contain a complete reading frame for a protein kinase C molecule. The diverse heterogeneity of the enzyme seems to be an important factor in determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(77 citation statements)
references
References 19 publications
5
72
0
Order By: Relevance
“…A full length % 3-kb cDNA (APKC-6) was obtained. It showed an identical restriction map and sequence identity to the cDNA isolated by Ono et al [8] (data not shown). A fragment containing the coding region of APKC-8 was subcloned into the mammalian expression vector pmt2 in the sense (pmt2 -PKC-GS) and antisense (pmt2 -PKC-GAS) orientations.…”
Section: Expression Of Pkc-8 In Cos-i Cellssupporting
confidence: 54%
See 1 more Smart Citation
“…A full length % 3-kb cDNA (APKC-6) was obtained. It showed an identical restriction map and sequence identity to the cDNA isolated by Ono et al [8] (data not shown). A fragment containing the coding region of APKC-8 was subcloned into the mammalian expression vector pmt2 in the sense (pmt2 -PKC-GS) and antisense (pmt2 -PKC-GAS) orientations.…”
Section: Expression Of Pkc-8 In Cos-i Cellssupporting
confidence: 54%
“…The library (2 x lo6 plaque-forming colonies) was screened using a 38-bp oligonucleotide probe based on nucleotides 817 -854 of PKC-6 [8]. The hybridization conditions used were as previously described [lo] except that the hybridization was carried out for 16 h at 42°C and the filters washed twice for 5 min at 42 "C and once for 10 min at 60°C.…”
Section: Isolation Of Cdna Encoding Pkc-6mentioning
confidence: 99%
“…The protein kinase C (PKC) family of multifunctional serine/threonine protein kinases consists of at least 12 family members which are widely distributed in eukaryotes [1][2][3]. Among those PKC ~x [2], a 'classical' (cPKC) Ca2+-dependent isoform, and PKC 8 [3], a 'novel' (nPKC) Ca2+-independent isoform are present in most central nervous and peripheral cell types [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among those PKC ~x [2], a 'classical' (cPKC) Ca2+-dependent isoform, and PKC 8 [3], a 'novel' (nPKC) Ca2+-independent isoform are present in most central nervous and peripheral cell types [1,4]. Prolonged activation of PKC c~ by phorbol esters caused a rapid loss of PKC enzyme activity and protein while PKC cx-mRNA was not affected in several studies [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Beside the four subspecies found previously in the mammalian brain, three additional members of rat protein kinase C family have also been described [7][8][9]. In the brain three major types of protein kinase C isoenzymes have been resolved by hydroxyapatite chromatography [10][11][12] and the correspondence of type I, II and III isoenzymes to the cDNA clones designated 7, 13x+/~ II and a, respectively, has been determined [13].…”
Section: Introductionmentioning
confidence: 88%